Short-term effects of post-fire salvage logging on runoff and soil erosion - Malvar, Maruxa C. (2020)
Research has been undertaken on the hydrological and erosional impact of forest fires, but remarkably little work has been conducted on salvage logging operations that often follow them. We assessed the effects of mechanical salvage logging following wildfire on soil physical properties, ground cover, and runoff and erosion response on a eucalypt stand in Portugal. We compared two levels of mechanical disturbance, skid trails by a wheeled forwarder tractor (“skid_low”) and skid trails by the same tractor followed by a tracked feller-buncher (“skid_high”) with control conditions (no mechanical disturbance). Three plots (16 m2) by level of soil disturbance were installed after a moderate intensity fire and subsequent logging operations, and monitored during the first post-fire year. In two control and two skid_low plots runoff was also measured. Soil bulk density was higher with increasing mechanical disturbance. Soil compaction reduced porosity 7–16%, but as the control porosity was 70%, the reduced porosity still was 60–65%. Soil resistance to penetration significantly increased for the most disturbed area, whereas soil shear strength was significantly reduced in the intermediate disturbance level. Mechanical disturbance did not induce significant effects on soil moisture or ground cover. Initial greater coverage by bare soil in the disturbed plots compared to the control was compensated by a more rapid vegetation recovery in those plots. Annual runoff amount was not higher at the skid-low than at control plots. Absence of runoff difference was due to high soil porosity of 65%, even after tractor trafficking, and a greater surface roughness on the skid_low plots compared to the control. Sediment production increased with increasing soil disturbance. The mean sediment rate was 1.6–3 times greater for the disturbed than the control plots. This increase could be explained by the higher soil compaction and reduced soil shear strength on the mechanically disturbed plots and initial differences in ground cover. Organic matter content of the eroded sediments was higher on the control than the disturbed plots, due to initial higher ash cover on the control plots. Overall, sediment production was significantly related to rainfall intensity and reduced by vegetation regrowth. Sediment rates tend to decrease with time since the initial fire and logging disturbance, highlighting the importance of a rapid implementation of erosion control measures. Specific management practices are needed to minimize the impacts of logging in burnt soils which are already subject to greater erosion risk and soil degradation.